(untitled) (International journal of artificial intelligence, 2026)
This study analyzes proverbs containing numerical components, which constitute important examples of Uzbek folk paremiology, particularly those found in Gulkhaniy’s work “Zarbulmasal”. The research reveals that numbers in proverbs function not only as quantitative elements but also convey symbolic, cognitive, cultural, and axiological (evaluative) meanings. It is established that through numbers such as “one”, “two”, “eight”, “nine”, “thirty”, “forty”, “thousand” proverbs express the people’s worldview, life experience, moral and normative values, and social relations. Furthermore, the study scientifically substantiates that numbers, acting as linguosemiotic units, enhance the expressiveness of proverbial meaning and ensure imagery and conciseness. The research findings are of significant importance for Uzbek paremiology, linguoculturology, and cognitive linguistics.